2008
DOI: 10.1029/2007jf000784
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic roughness lengths over movable beds: Comparison of wind tunnel and field data

Abstract: [1] We evaluate the increase in apparent roughness length during aeolian saltation. Using a data set comprising 291 wind profiles measured in wind tunnels or in the field, we tested the Charnock (1955), modified Charnock (Sherman, 1992), and Raupach (1991 relationships for the entire data set and for segregated wind tunnel and field data sets. We assessed the abilities of the models to predict enhanced roughness and investigated scaling differences between wind tunnels and field environments. For the entire da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
100
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(112 citation statements)
references
References 78 publications
(131 reference statements)
11
100
1
Order By: Relevance
“…As shown in Fig. 7, plots at point F scattered around the logarithmic law curve of c 0 = 0.05 and those at point C scattered around the curve of c 0 = 0.29, indicating that the law with the Charnock constant could be applied to the profile at the measurement points; these values are similar to values at a range of 0.01 to 0.24 in fields (Sherman and Farrell 2008). c 0 at point C was six times as large as that at point F. This could indicate that c 0 over slope was larger than that over flat.…”
Section: Wind Forcing Over Flat and Slopesupporting
confidence: 65%
See 1 more Smart Citation
“…As shown in Fig. 7, plots at point F scattered around the logarithmic law curve of c 0 = 0.05 and those at point C scattered around the curve of c 0 = 0.29, indicating that the law with the Charnock constant could be applied to the profile at the measurement points; these values are similar to values at a range of 0.01 to 0.24 in fields (Sherman and Farrell 2008). c 0 at point C was six times as large as that at point F. This could indicate that c 0 over slope was larger than that over flat.…”
Section: Wind Forcing Over Flat and Slopesupporting
confidence: 65%
“…c 0 is Charnock constant, for which Raupach (1991) gave 0.02 for wind tunnel experiments and 0.16 for beaches. Sherman and Farrell (2008) demonstrated that the…”
Section: Wind Forcing Over Flat and Slopementioning
confidence: 99%
“…First, we take into account the effect of saltation. On a flat surface, z 0 is a function of both the grain diameter and the excess shear velocity and can be approximated by [Sherman and Farrell, 2008] …”
Section: Resultsmentioning
confidence: 99%
“…They found that shrubs bunched into patches resulted in far greater sediment fluxes than in the case of regular grids of single shrubs, likely because of a significant increase in turbulence between the patches. However, the length scales of saltation in wind tunnels has been shown to differ from those of natural saltation [128][129][130], so findings from wind tunnel studies should be treated with some caution.…”
Section: Evidence From Wind Tunnel Windbreak and Field Studiesmentioning
confidence: 99%